Translation strategies in Shakespeare's Romeo and Juliet translated drama script viewed from the romance perspective - Wulandari Dwipuspita; Prilla Lukis Wediyantoro (Universitas Merdeka Malang, 2023)
Romeo and Juliet is one of Shakespeare's most famous masterpieces, translated into many languages. This study's object is the drama script of Romeo and Juliet translated by Fatimah, Ifa Nabila, and Ratna Ofvilia (2018). In this study, the writers employed the descriptive qualitative approach to figure out the translation strategies used to translate the figurative language viewed from the romance aspects. The results revealed that the translators used six translation strategies: modulation, transposition, addition, subtraction, descriptive strategy, and literal translation. Besides, the writers also found 12 data of figurative language: five metaphors, four hyperboles, three personifications, one allusion, and one simile.